(untitled) (Revista Argentina de Cirugía, 2026)
Background: The COVID-19 pandemic poses an unprecedented challenge to surgical education worldwide. The lack of hands-on activity, due to suspensions and restrictions, jeopardizes the ability of training programs to meet the competence standards required for the practice of the specialty. Objective: To compare residents’ surgical activity before and during the lockdown, and describe the changes in healthcare roles and training strategies. Material and Methods: We conducted a descriptive, observational and retrospective study. The surgeries performed by residents during pre-pandemic (March 2019-February 2020) and intrapandemic (March 2020-February 2021) periods were recorded. The number and type of procedures and the year of the residency program were compared in both periods. The percent change in outpatient consultations was also analyzed. Results: The total number of plastic surgery procedures was reduced by 59% (n = 368 vs. n = 152). Scheduled cosmetic procedures decreased by 64%. Reconstructive procedures decreased by 55%: skin tumors -64%, breast reconstruction -54%, extremity reconstruction -40%, head and neck reconstruction -13%. Multidisciplinary reconstructions performed with other specialists showed different patterns. Face-to-face consultations decreased by 50% (n = 2603 vs. n = 1308). Conclusions: During the lockdown, there was a marked decrease in all the types of surgical and healthcare activities among residents in plastic surgery which will influence their training, posing a challenge to minimize this impact.